Design of an application for community reporting system - Roslan, M.Ridzuan; Ahmad Zabidi, Suriza (IEEE, 2019)
A community reporting system is a system that allows the user to report any misconduct to the relevant authority, easily and hustle free. The problem with the the existing system is inefficient and time-consuming. The system makes the user unwilling to make a report to the authority. The objective of this project is to design a system using an android application that is cost-effective and easy to use. The scope of this project is on the road violation reporting system. The outcome of the system will provide a user with an easy reporting system and also the authority can manage the report easily. The development of the system